The role of art in society (The Peerian Journal, 2024)
In this article, the main focus in educating each artist should be on his higher goal and skills. The peculiarities of art are determined by the tools used: vocabulary, elegant linnicutions, shapes, colors, movements. It discusses the extent to which art plays a role in society